Subcutaneous Emphysema - Woehrlen, Arthur E. (1985)
This case describes the development of subcutaneous emphysema following restorative dentistry performed under general anesthesia. Initial treatment consisted of intravenous epinephrine and dexamethasone due to difficulty in breathing and laryngeal stridor. Dexamethasone and other adjunctive drugs were administered over the 4 days following surgery while the symptoms subsided. The author emphasizes the importance of early recognition and prompt management in managing this unusual complication.